TRANSFORMATIVE ECOFEMINISM MOVEMENT IN EMPOWERING INDONESIAN WOMEN - Clara, Evy (PEOPLE: International Journal of Social Sciences, 2018)
This research has a purpose to analyze Women’s Journal Foundation as an organization of women who performs the environmental movement and the empowerment of women (ecofeminism) through the Journal. This research used a critical paradigm, a qualitative approach and phenomenological designs. The research locations were held in Jakarta, Salatiga, and Klaten, and took time for 23 months (August 2013 - June 2015). The result showed that: (1) Women Journal Foundation was founded in 1995 by Gadis Arivia with the goal of advancing gender equality; (2) it innitially lied on feminist ideology, a courage to build women’s awareness through women journals as the essential movement media; (3) instrument of Women Journal Foundation movement is Friends of Women Journal, performing financial strengthening while providing ecofeminism awareness, and raising ecofeminism in the practical level; and (4) the implications of the movement Women Journal Foundation are the growth of ecofeminism awareness that manifests itself into empowerment of women who care about garbage (Garbage Bank) in Salatiga and natural dye used for batik in Klaten.